Optical and nonlinear optical properties of Zn0.96Cu0.04Al2O4 nanocomposites prepared by combustion method. (2021) - Surendran, P.; Lakshmanan, A.; Sakthy Priya, S.; Balakrishnan, K.; Hegde, Tejaswi Ashok; Vinitha, G.; Ramalingam, G.; Rameshkumar, P.; Kaviyarasu, K.
Abstract: Nano - sized Zn0.96 Cu0.04 Al2 O4 powder was synthesized by microwave- assisted combustion technique. The structural and morphological properties of the title compound were characterized by Powder X-ray diffraction (XRD) and High-Resolution Transition Electron Microscopy (HRTEM). XRD results enunciate that the nanoparticle crystallizes in cubic spinel structure with average crystallite size (17.18 nm) and specific surface area 75.2866 (m 2 /g). In the HRTEM image shows spherical shape in nature. From the luminescence spectrum, the energy bandgap value was calculated as 2.973 eV. The nonlinearity studies of Zn/Cu/Al2 O4 nanoparticles were measured by Z-scan technique. This technique was used to calculate the third-order nonlinear optical parameters such as nonlinear absorption coefficient (β), nonlinear refractive index (n2 ) and third-order nonlinear susceptibility (χ (3) ).